Economic growth and development: the need for a convergent approach - Gamero Requena, Julio (2008)
Peru needs a new institutional arrangement aimed at redistribution, including universal coverage of essential benefits guaranteed to all and corresponding to the country's levels of development. This means reviewing the liberal reforms proposed by the Washington Consensus, whose ideological parameters favored the precariousness of employment and the persistence of poverty conditions pending uncertain development. This article summarizes such approaches, which go beyond the focus of social policies.